Comparative virulence of microbial bioagents against castor spiny caterpillar, Ariadne merione (Lepidoptera: Nymphalidae): Comparative virulence of microbial bioagents against castor spiny caterpillar, Ariadne merione (Lepidoptera: Nymphalidae) - E BHARATHI; P DURAIMURUGAN (Journal of Oilseeds Research, 2023)
The castor spiny caterpillar, Ariadne (Ergolis) merione is one of the major insect pests of castor. Microbial bioagents offer considerable promise for eco-friendly insect pest management. Hence, pathogenicity of the entomopathogenic bacteria and fungi were evaluated against larvae and pupae of A. merione under laboratory conditions. Among the microbial bioagents, entomopathogenic fungi, Beauveria bassiana recorded high pathogenicity against A. merione larvae followed by entomopathogenic bacteria, B. thuringiensis. The LC50 of B. bassiana and B. thuringiensis against A. merione larvae was 0.89 and 1.18 g/l, respectively. B. bassiana @ 2 g/l effected pupal mortality and pupal malformation, while M. rileyi did not cause any pupal mortality. Hence, B. bassiana and B. thuringiensis can be used in IPM programme as a potential microbial bioagents against castor spiny caterpillar in castor.